Development of augmented reality-based learning media to improve student learning outcomes in the subject of electric motor installation at SMK Negeri 2 Yogyakarta - Jan Foxsechar Silalahi; Sunaryo Soenarto (ARKA INSTITUTE, 2023)
In the Electric Motor Installation material there are limitations in the form of requiring the physical form of components to introduce components directly. The development of learning media developed is Electric Motor Installation Learning Media for augmented reality-based learning to overcome limitations and provide alternative learning resources that so far teachers have used conventional learning media. The developed learning media includes 3-dimensional electric motor installation components displayed with augmented reality technology. The method in this study is research and development with the ADDIE model. Preliminary studies were conducted by analyzing the needs of basic competencies using questionnaires and interviews. Testing the effectiveness of learning media and knowing learning outcomes is carried out using the post-test and pre-test methods which produce valid values for 30 items above the value of 0.30 and reliable above 0.6. The results of the effectiveness test obtained a percentage of 56-75 percent so that this learning media was declared effective. Student responses to the feasibility of learning media showed that 20 students stated that it was very feasible and 10 students stated that it was feasible so that they concluded that learning media was feasible for use in learning Electric Motor Installation.